The History and Economics of Melaleuca Management in South Florida - Katherine Carter-Finn; Alan W. Hodges; Donna J. Lee; Michael T. Olexa (EDIS, 2006)
FE670, a 4-page fact sheet by Katherine Carter-Finn, Alan W. Hodges, Donna J. Lee, and Michael T. Olexa, provides an overview melaleuca in South Florida, the economic damages and management history. Includes references. Published by the UF Department of Food and Resource Economics, November 2006.